Long-Term Follow-Up of Single-Fiber Multiple Low-Intensity Energy Laser Ablation Technique of Benign Thyroid Nodules - Squarcia, Mattia; Mora, Mireia; Aranda, Gloria; Carrero, Enrique; Martínez, Daniel; Jerez, Ramona; Valero, Ricard; Berenguer, Joan; Halperin, Irene; Hanzu, Felicia A. (Frontiers in Oncology, 2021)
Aim: The short-term and long-term efficacy of different thermal percutaneous ablation techniques remains a topical issue. Our group implemented percutaneous laser ablation (LA) - a moving shot technique to increase efficiency, reduce costs and variability of LA by applying multiple lower intensity energy illuminations (MLIEI) covering the nodular volume (V) through changes in position of a single laser fiber within the nodule. The aim was to evaluate the efficacy of the single fiber LA-MLIEI during a 5-y follow-up and to identify possible predictors of the outcome. Methods: Prospective study: Thirty outpatients (23 w/7m) with benign symptomatic thyroid nodules were assigned between 2012- 2015. A single LA session was performed US guidance using a 1064nm continuous wave laser at 3W. A 400µm optical fiber was inserted through a 21G needle, and 3-10illuminations were performed per nodule, administrating between 400-850J / illumination. Total energy was calculated on the initial V of the nodule and the estimated ablation area. US was performed after LA-MLIEI at 1 w, 1-, 3-, 6-, 12-m and annually up to 5-y. Clinical symptoms, thyroid function and acute and chronic complications of treatment were registered. Results: On follow-up, 67% (n: 20) were responders while 33% (n: 10) were non-responders. Responder group initiated V reduction (V) at 1 m, with remission of symptoms, and presented a 50% V at 3m of treatment; the maximum response was achieved at 24m, and remained stable until the end of the study. Non-responder group presented a V of less than 50% at 12m; though a tendency to >50% V was observed at 24–36m, there was subsequent regrowth, and 40% of this group required surgery. V was positively correlated with the total administered energy/V (J/V) and inversely with nodule V. No severe adverse effects were observed. Thyroid function remained normal in all patients. Remission of symptoms occurred rapidly after 1 m. Conclusions: LA-MLIEI a single fiber in a unique session is a safe and inexpensive technique allows rapid reduction of thyroid nodules, with a stable response up to 5 y, similarly to conventional LA. Total nodule V appears as a predictive factor of the reduction.